1987
DOI: 10.1067/mva.1987.avs0050248
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous arterial perforation: The Ehlers-Danlos specter

Abstract: The Ehlers-Danlos syndrome (EDs) is one of the most frequently inherited disorders of connective tissue. Type IV EDs, the arterial-ecchymotic type, is of concern to vascular surgeons because it is frequently associated with spontaneous catastrophic bleeding. This article summarizes our experience with five members of a family and reviews the 31 patients with type IV EDs described in the literature. The 22 male and 14 female patients had a mean age of 26 years. The 36 patients included 23 with easy "bruisabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 0 publications
0
48
0
2
Order By: Relevance
“…4,10,23,31) In this case, it was judged that the risk of performing intravascular catheter operation by the fragile of a vessel wall was very high. We gave up performing some inspection of monitoring before operation, such as cerebral blood flow study with balloon occlusion examination, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…4,10,23,31) In this case, it was judged that the risk of performing intravascular catheter operation by the fragile of a vessel wall was very high. We gave up performing some inspection of monitoring before operation, such as cerebral blood flow study with balloon occlusion examination, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…9 In the general population, angiography carries a risk of 2.5% morbidity, but in patients with EhlersDanlos type IV, angiography has been associated with morbidity rates of 36%-67% because of the increased risk of carotid dissection, arterial perforation, and hematoma. 4,10 Both the transarterial and transvenous approaches carry these high risks because of the fragility of the vessels. Arteries in these patients are also often more tortuous, making it difficult to navigate a catheter through the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…One case series examining 31 family members with Ehlers-Danlos aortic disease revealed that 8 of 12 patients who underwent percutaneous diagnostic or interventional angiographic procedures had access site complications, including 2 deaths. 64 Other literature supports open femoral artery exposure for any endovascular procedure to primarily repair the diseased artery in a tension-free fashion, often with Teflon felt pledgets or cuffs. 65,66 With the high number and frequency of vascular complications in these patients during open femoral exposure for endovascular access, it is not surprising that no one has been eager to attempt percutaneous aortic interventions.…”
Section: Percutaneous Management Of Aortic Dissectionmentioning
confidence: 99%